The Political Impact of Chewing Khat (Chat) on Chewers: In the Case of Woldia City Administration of North Wollo, Amhara National Regional State - Agenagn Kebede; Belay Asmare; Admasu Bogale (Britain International for Academic Research (BIAR-Publisher), 2021)
The main aim of this study was to investigate the political impact of chewing khat on the chewers in Woldia City Administration of North Wollo, Amhara National Regional State. As far as the researcher's reading, no research was conducted in Ethiopia dealing with the political impact of chewing khat on chewers. Accordingly, this study was conducted using qualitative methods of data collection. Semi-structured in-depth interview, focus group discussion (FGD), and complete observation were employed during data collection. The study used phenomenology design and the findings were analyzed thematically. The study found that khat chewers’ political unconsciousness, utopian involvement in politics, and fail in conspired politics were associated with khat chewing practices. Based on this findings, the researchers recommend that awarness creation about the anxiety of khat in political life is in need.